KRITIK EKOLOGIS DALAM LAGU DAERAH BIMA KARYA CUCU MALINGI: KAJIAN EKOKRITIK DAN CRITICAL DISCOURSE ANALYSIS - Ifan, Muhammad; Sulistiana, Evi; Iryani, Evi; Taufiq, Ahmad (HISKI, 2025)
Environmental degradation, including deforestation, wildlife extinction, and ecological disasters, constitutes a serious issue that necessitates interdisciplinary attention. This study examines ecological criticism represented in the traditional Bima song “Nggahi Rawi Pahu” by Cucu Malingi through the lens of ecocriticism and Critical Discourse Analysis (CDA). The analytical framework combines Greg Garrard’s ecocritical concepts (apocalypse, pollution, and animals) with Teun A. van Dijk’s AWK model (text structure, social cognition, and sociocultural context) to investigate the song lyrics as a medium of critique against environmental exploitation. The findings indicate that the lyrics construct a narrative of ecological damage through the use of symbolism, repetition, and metaphor, which illustrate deforestation, the extinction of wildlife, and flooding as direct consequences of human activity. Furthermore, the discourse strategies employed in the text foster collective ecological awareness and ideological resistance to environmental destruction by grounding the message in local cultural knowledge. This study highlights the role of traditional songs not merely as cultural expressions, but also as vehicles for ecological critique and public consciousness-raising.Keywords: Ecological Criticism, Critical Discourse Analysis, Traditional Song, Bima, Environmental Degradation AbstrakKerusakan lingkungan seperti deforestasi, kepunahan satwa, dan bencana ekologis menjadi persoalan yang memerlukan perhatian lintas disiplin. Penelitian ini menganalisis kritik ekologis yang direpresentasikan dalam lagu daerah Bima berjudul “Nggahi Rawi Pahu” karya Cucu Malingi dengan menggunakan pendekatan ekokritik dan critical discourse analysis (CDA). Pendekatan ekokritik Greg Garrard (apocalypse, pollution, dan animals) serta model AWK Teun A. van Dijk (struktur teks, kognisi sosial, dan konteks sosiokultural) digunakan untuk mengkaji lirik lagu sebagai bentuk kritik terhadap eksploitasi lingkungan. Hasil analisis menunjukkan bahwa lirik lagu membentuk narasi kerusakan ekologis melalui simbolisme, repetisi, dan metafora yang menggambarkan penggundulan hutan, punahnya satwa, dan banjir sebagai dampak langsung aktivitas manusia. Selain itu, strategi wacana dalam teks membangun kesadaran ekologis kolektif dan resistensi ideologis terhadap kerusakan lingkungan dengan mengandalkan pengetahuan budaya lokal. Penelitian ini menegaskan bahwa lagu tradisional tidak hanya sebagai ekspresi budaya, tetapi juga sebagai medium kritik ekologis dan penyadaran publik.Kata kunci: Kritik Ekologis, Analisis Wacana Kritis, Lagu Tradisional, Bima, Kerusakan Lingkungan